Estratégias para reduzir as emissões gasosas e melhorar o aproveitamento do nitrogênio de dejetos de suínos pelo milho - Miola, Ezequiel César Carvalho (2014)
While promoting increased farm production, applications of pig slurry (PS), in notillage systems (NT), may represent an important source of environmental contamination. Therefore, the pursuit of technological strategies to minimize this potential polluter of DLS is one of the main current challenges in pig farming. Given this context, the aim of this study was to evaluate how the subsurface injection of PS in NT and the use of the nitrification inhibitor dicyandiamide (DCD) affects emissions of nitrous oxide (N2O), N losses by ammonia (NH3) volatilization and nitrogen (N) supply to corn. The study was conducted at the Federal University of Santa Maria during the growing seasons of corn in 2011/12 and 2012/13. Two experiments were conducted, one in a Typic Paleudult (Site I) and another in a Typic Paleudult (Site II). In both sites, we used the experimental design of randomized blocks with four replications of the following treatments: Pig slurry surface (PSs), PSs + DCD, pig slurry injected into the subsurface (PSi), PSi + DCD, control without fertilizers or DCD (Control) and mineral fertilization (urea). The injection of PS reduced NH3 emissions by 70%, but increased N2O-N from 2.628 to 6.198 g N2O N ha-1, compared to surface application. The addition of DCD to PS, at the time of its application to the soil, reduced N2O emissions by 28% when the PS were applied on the soil surface and 66% when injected, but did not influenced the emissions of NH3. The emission factor (EF) of N2O was higher when the PS were injected (3.6%) than when applied to the surface of the soil (1.3%), whereas the DCD reduced such EF to 0.9% and 0.8%, respectively. The injection of PS in the soil increased N use efficiency and the yield of corn grains compared to surface application, while the DCD did not affect these two attributes. When N2O emissions from each treatment were related to corn yield, the best results from an environmental point of view were obtained when the injection of PS was associated with the use of DCD. From these results it is concluded that the injection of PS in the soil under NT associated with DCD, is a promising alternative compared to current technology for the application of PS on the soil surface and without DCD. However, this strategy can only be recommended and widespread safely to producers if their agronomic and environmental benefits are followed by an economic analysis as well as an analysis of the environmental impact of the additional demand for energy and fuel to make the mechanical operation injection of PS in the soil.